Do accounting standards matter for foreign direct investment in developing countries? - Owusu, Godfred Matthew Yaw; Mohd Saat, Nur Ashikin; K. Suppiah, Susela Devi; Law, Siong Hook (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This study investigates the macroeconomic implications of the adoption of International Financial Reporting Standards (IFRS) in developing countries. The current study specifically examines the relationship between IFRS adoption and Foreign Direct Investment (FDI) inflows to developing countries. A total of 116 developing countries with available data were used for the study analysis. A panel data averaged over three non-overlapping years from the period 1996-2013 for the sampled countries was used for the empirical analysis. The efficient two-step System Generalized Methods of Moment estimation technique with Windmeijer corrected standards errors and orthogonal deviations was employed to examine the empirical relations. Results from the dynamic panel GMM estimation demonstrate that IFRS adoption on its own does not affect the amount of FDI inflows to developing countries. This finding thus suggests that adopting IFRS alone may not be enough for developing countries to attract the much needed FDI inflows. Results from this study therefore calls for the need to further examine the conditions under which developing countries could harness the economic benefits of adopting the IFRS.